New record of Microtechnites bractatus (Say) (Hemiptera: Miridae) infesting Crotalaria spp. and injuries of Miridae in cultivated plants in the State of Paraná, Brazil - Ribeiro,Luana Karoline (2020)
Abstract This study reports for the first time the plant bug Microtechnites bractatus (Say) in Crotalaria juncea and Crotalaria spectabilis, in the state of Paraná, Brazil. We characterized the injuries caused by M. bractatus and Collaria scenica Stal in cultivated plants and in Crotalaria spp. Considering that M. bractatus damage has been incorrectly attributed to C. scenica, we present here a contribution to the correct characterization of these insect pests and their damage over some agricultural crops.